Climate change – psychology’s contribution - Spence, Alexa; Pidgeon, Nick; Uzzell, David (2009)
Climate change is a word on everybody’s lips at the moment. But, what role can we, as psychologists, both individually and within our sub-disciplinary groups play in reducing and adapting to the impacts of society’s ‘carbon footprint’? This article argues that the issue of climate change raises an important set of research and public policy questions which psychologists are well placed to help address. In particular, we focus on the issues of sustainable behaviour change and nuclear power.